Pengaruh Servqual Terhadap Akuntabilitas Masjid Di Masa Pandemi Covid 19 - Muhammad Yusran; Jumardi Jumardi (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2022)
ABSTRACT The purpose of this study was to analyze the accountability of mosques based on the quality of service to the community during the Covid 19 pandemic in West Sulawesi Province. The study used a quantitative approach with the purposive sampling technique which was analyzed by multiple regression. Data were obtained using a questionnaire with 188 respondents. The results showed that the servqual variables Professional Skill (X1), Attitudes and Behavior (X2), Accessibility and Flexibility (X3), Realiability and Trustworthiness (X4), Reputation and Credibility (X6) had a significant influence on mosque accountability. Simultaneously, all servqual variables have a significant effect on mosque accountability. While the variable Servqual Recovery (X5) does not have a significant effect on the accountability of the mosque. This is due to the health financial aspect, many administrators or community leaders and the surrounding environment neglect to implement strict health protocols. Many people tend to ignore health prevention and control standards during the Covid-19 pandemic. Key Word: Mosque Accountability, Servqual, Covid 19 Pandemic